Тreatment of uterine cervical dysplasia on the background of hyper proliferative disease of the corpus uteri in women of reproductive age - В. К. Кондратюк; Н. Є. Горбань; Н. П. Дзісь; А. І. Нарольська (Publishing House TRILIST, 2017)
The work is devoted to increasing the effectiveness of treatment the dysplastic lesions of the cervical epithelium (DLCE) on the background of hyper proliferative diseases of the uterine body (HDUB) in women of reproductive age by developing a complex of diagnostic and therapeutic measures based on the study of clinical, cytological, colposcopy, microbiological, virological, morphological and immune histochemical features of the cervical epithelium. The results of treatment of 90 women of reproductive age with DLCE on the background of HDUB were analyzed. Criteria for inclusion of patients in the study: CIN I, CIN II, CIN III, uterine leiomyoma, endometriosis of the uterus, papillomaviruses. Women of the main group (45 patients) received the developed diagnostic and treatment complex. The comparison group consisted of 45 patients, whose treatment was performed in accordance with regulatory documents. Subject to confirmation of the inflammatory process of the pelvic organs, the participants of the study performed complex anti-inflammatory therapy (antibacterial, antiviral) taking into account the antibioticogram on the background of the immunomodulator, as well as antifungal, desensitizing, hepatoprotective and enzyme therapy. In particular, the immunomodulator tilorone and local anti-inflammatory treatment were used. Four weeks after the end of the conservative treatment, the elimination of pathogens and normalization of the microbiocenosis in 77.8% of the patients of the main group and in 64.4% of the women of the comparison group was confirmed. In 33.3% of the women of the main group and 31.1% patients of the comparison group radio wave conization of the cervix was performed. For the prevention and treatment of intra- and postoperative bleedings during the surgical treatment of DLCE an anti-fibrinolytic drug was used. To improve the regenerative properties and prevent recurrence of DLCE in the postoperative period rehabilitative treatment with vaginal suppositories containing 100 mg of dexpanthenol and 16 mg of chlorhexidine bigluconate was used. As the authors of the study noted, the use of complex of diagnostic and therapeutic measures in women of reproductive age with DLCE on the background of HDUB contributed to increase of the effectiveness of DLCE surgical treatment in 1.2 times, which allowed to safely use hormonal treatment of hyper proliferative pathology of the uterus body.